Analisis Sistem Pengelolaan Dana Jaminan dan Pembayaran Klaim pada BPJS Ketenagakerjaan Cabang Medan Kota Dalam Perspektif Manajemen Keuangan Syariah - Putri, Annisa; Lubis, Fauzi Arif; Hasibuan, Reni Ria Armayani (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This study aims to find out and analyze the system of financial management and payment of claims at iBPJS iKetenagakerjaan iMedan iKota branch in accordance with the principles of Islamic financial management. This research uses idescriptive qualitative research methods, i.e. research that is verbally stated as an irresistible respondent. There are two sources of data from this research, i.e. primary data sources and secondary data sources. The results of this study indicate that regarding the management of iBPJS iKetenagakerjaan iMedan iKota branches, if viewed from the perspective of Islamic financial management, it is not yet in accordance with overall. In the view of Islamic financial management, this system of financial management must have three criteria, namely avoidance of igharar, immaysir and iriba. The principle of igharar idi iBPJS iKetenagakerjaan iMedan iKota ibranch does not exist because iBPJS is an iPublic iLaw Agency which is directly assigned by the state to provide isocial security protection iemployment to iIndonesian workers who have the principle of iplease help. The principle of immaysir if seen from the ownership of funds cannot be found because the contributions of the participants will become social funds which will be invested by the financial manager of the central office. If the participant stops being a participant, the contribution will not be forfeited and the claimant can claim it in accordance with the existing requirements. iRiba iPrinciples iBPJS iEmployment is still attached because participants' contributions are still being invested in non-sharia investment instruments. According to the Islamic review, the procedure for submitting claims can be accepted in Islam because the practices or actions that can bring benefits to many people are justified in Islam.